A pspice-based design of DC-DC converter systems - Muhamad, Nik Din; Mohd. Yatim, Abdul Halim; Shafie, Abd. Jaafar (IEEE, 2004)
A new approach to using Pspice in designing dcdc converter systems is introduced in this paper. In this new approach, the power stage and control loop design equations are programmed in Pspice. For this purpose, an option available in Pspice called Analog Behavioral Modeling (ABM) is used. By doing so, the parameter of power stage and the component values of the error amplifier can be easily obtained by means of Pspice DC analysis. The methodology of development is presented in some detail. A design example is included to demonstrate the effectiveness of the proposed approach In designing dc-de converter systems.